2008
DOI: 10.1177/1063426608319141
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Behavioral Problems Reported in Child Welfare Over 3 Years

Abstract: Child welfare agencies are required to provide services that ensure that children receive adequate mental health care. This study provides a comprehensive view of the emotional and behavioral problems of children who are referred to child welfare services, using nationally representative data. Bivariate analyses compare rates by child demographics, and conditional probability tables present changes in clinical status. Results show that 62% of children have at least one clinical-level score over 3 years. Rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 43 publications
2
29
0
2
Order By: Relevance
“…Recently it has been shown that children and adolescents that have experienced maltreatment suffer from more emotional problems than the general population (Buckingham & Daniolos, 2013;McCrae, 2009). These young people also demonstrate cognitive deficits relative to youth that have not been maltreated (Beers & De Bellis, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Recently it has been shown that children and adolescents that have experienced maltreatment suffer from more emotional problems than the general population (Buckingham & Daniolos, 2013;McCrae, 2009). These young people also demonstrate cognitive deficits relative to youth that have not been maltreated (Beers & De Bellis, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Youth with behavior disorders are highly represented in systems of care, 29 Child Welfare, 30 Education, 31 and Juvenile Justice. 32 Research also suggests that youth with behavior problems are at higher risk for restrictive and out-of-home placements than their peers with emotional disorders.…”
Section: Service System Involvement As a Correlate Of Delinquencymentioning
confidence: 99%
“…Children removed from the home by child welfare services generally exhibit poorer mental health outcomes (Grogan-Kaylor, Ruffolo, Ortega, & Clarke, 2008; Leslie et al, 2000; McCrae, 2009). Research shows African American youth are disproportionately involved in the child welfare system, and these youth experience greater rates of child abuse and neglect as well as the associated negative impacts on mental health (Ards, Myers, Malkis, Sugrue, & Zhou, 2003).…”
Section: Overviewmentioning
confidence: 99%